Iliac Seal Zone Dynamics and Clinical Consequences After Endovascular Aneurysm Repair. (February 2017) - Bastos Gonçalves, F.; Oliveira, N.F.; Josee van Rijn, M.; Ultee, K.H.J.; Hoeks, S.E.; Ten Raa, S.; Stolker, R.J.; Verhagen, H.J.M.
Abstract : Objective: To evaluate the dynamics of the iliac attachment zone after EVAR, and the association with clinical events. Methods: A tertiary institution's prospective EVAR database was searched to identify common iliac arteries at risk. Internally validated measurements were made, using centre lumen line reconstructions. Iliac dilatation and endograft limb retraction were the main endpoints. Associations between dilatation, retraction, oversizing, and distal seal length were investigated. Association with clinical events (sealing or occlusion) was also explored. Results: Of 452 primary EVAR patients treated from 2004 to 2012, 341 were included (mean age 72 years, 12% female, 597 common iliac arteries). Median follow-up was 4.7 years. At 30 days, the mean iliac diameter increased from 14 mm to 15 mm ( p  < .001). Over follow-up, it increased to 18 mm ( p  < .001). Iliac dilatation ≥20% occurred in 295 cases (49.4%) and exceeded the implanted endograft diameter in 170 (28.7%). Limb retraction ≥5 mm was identified in 54 patients (9.1%) and was associated with iliac seal complications ( p  < 0.001). Iliac endograft extension diameter ≥24 mm (OR 3.3, 95% CI 1.7–6.4) and iliac artery dilatation beyond the endograft (OR 2.1, 95% CI 1.2–3.8) were independent risk factors. Overall, there were 34 (5.7%) iliac seal complications. Retraction of the iliac endograft (OR 1.17 per mm, 95% CI 1.10–1.24) and baseline AAA diameter (1.04 per mm, 95% CI 1.01–1.07) were independent risk factors for seal related complications. Greater initial post-operative iliac seal length was protective (OR 0.94 per mm, 95% CI 0.90–0.97). Conclusions: Iliac dilatation and endograft retraction are common findings during follow-up, potentially leading to adverse clinical events. Optimisation of the iliac seal zone providing a long distal seal length and added attention to patients with large aneurysms or receiving ≥24 mm diameter iliac extensions are recommended. Also, long-term surveillance including CTA is advised to reveal and correct loss of seal at the iliac attachments before adverse clinical events occur.